2015
DOI: 10.4103/1463-1741.155845
|View full text |Cite
|
Sign up to set email alerts
|

The impact of road traffic noise on cognitive performance in attention-based tasks depends on noise level even within moderate-level ranges

Abstract: Little empirical evidence is available regarding the effects of road traffic noise on cognitive performance in adults, although traffic noise can be heard at many offices and home office workplaces. Our study tested the impact of road traffic noise at different levels (50 dB(A), 60 dB(A), 70 dB(A)) on performance in three tasks that differed with respect to their dependency on attentional and storage functions, as follows: The Stroop task, in which performance relied predominantly on attentional functions (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 47 publications
1
27
0
1
Order By: Relevance
“…Cognitive interference seems directly involved in auditory processing. Behavioral data suggest that less cognitive interference is related to better speech recognition in noise at more difficult signal-to-noise ratios (Stenbäck et al, 2016), and cognitive interference in the visual modality increased when performing the tasks in noise (Schlittmeier et al, 2015). Whereas the studies discussed in the previous section suggest that cognitive load could affect the ABR by way of cognitive inhibition and sensory gating, none of those studies directly considered cognitive interference as a measure of cognitive inhibition.…”
Section: Introductionmentioning
confidence: 97%
“…Cognitive interference seems directly involved in auditory processing. Behavioral data suggest that less cognitive interference is related to better speech recognition in noise at more difficult signal-to-noise ratios (Stenbäck et al, 2016), and cognitive interference in the visual modality increased when performing the tasks in noise (Schlittmeier et al, 2015). Whereas the studies discussed in the previous section suggest that cognitive load could affect the ABR by way of cognitive inhibition and sensory gating, none of those studies directly considered cognitive interference as a measure of cognitive inhibition.…”
Section: Introductionmentioning
confidence: 97%
“…The methods used predicted that New York City had the highest number of vehicles and highest noise levels, followed by Los Angeles and Atlanta. In a study conducted by Schlittmeier et al [19] in Germany, they found that people are less annoyed with a road traffic noise 50dBA than a loud road traffic noise of 70dBA. In France, a study conducted by Méline et al [20] showed that there were relationships between transportation noise in the study area (workplace) and blood pressure.…”
Section: Trafficmentioning
confidence: 97%
“…A healthy sleep requires a quiet bedroom (Fietze et al, 2016). In office buildings, clerical activities such as reading, writing, typing, and holding meeting require NC 30-35 (equivalent to 40-45 dBA) (Long, 2014;Schlittmeier, Feil, Liebl, & Hellbrück, 2015). Although this is not as low as required in the residential building environment, office rooms still need low noise to support good-quality, productive workspaces.…”
Section: Outdoor Noise and Indoor Noise Criteriamentioning
confidence: 99%